Study of RTPPS algorithm in UWB communication medium for a surveillance system to protect agricultural crops from wild animals - Borah, Siddhanta; Kumar, R.; Mukherjee, Subhradip (2020 IEEE International Symposium on Smart Electronic Systems (iSES) (Formerly iNiS), 2020)
Ultra-wide band communication medium is for fast speed and high date rate communication [1] In this paper, a unique algorithm named "Real Time Pixel by Pixel Subtraction (RTPPS)" has been presented in ultra-wide band communication medium to protect agriculture crops from different wild animals in agriculture field. The algorithm is developed with less complexity such that it can consume less time to execute the algorithm. This algorithm is capable of taking preventive measures instantly based on the presence of wild animals in agriculture field. To design the system, Raspberry Pi 3 B+is used as a main controller unit that supports 2.4 to 5GHz IEEE 802.11.b/g/n/ac wireless local area network (WLAN). The algorithm is developed using image processing techniques in MATLAB 2018 version. The hardware prototype model was tested in different regions of Nagaland, India during the month of May-June 2020. During the testing of this device it was found that at a threshold value of 7710, this device can detect animals like wild buffalo, unfastened cow, wild pigs and macaques.